Scabies in Children: A Retrospective Study - Retha Retha; Sawitri Sawitri (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Scabies is a skin disease in humans and is caused by Sarcoptes scabiei mite. It burrows into the skin and is transmitted through close physical contact. The common symptom is itchiness, mainly occur at night, along with a history of itch from family members or friends with whom the patients might have close physical contact before. Scabies is still a concerning health problem for the majority of poor and developing countries. Purpose: To evaluate the profile of newly-admitted children scabies patients. Methods: This study retrospectively evaluated the medical records of subjects with scabies in the Children Dermatology Division, Dermatology and Venereology Department of Dr. Soetomo General Academic Hospital, Surabaya, between January 2012 and December 2014. Results: There were 545 patients with scabies (33.6% from Children Dermatology Division visit and 3.2% from overall outpatient clinic visit), mainly consisted of children aged 5-14 years old (69%), and mostly males (62.6%). The most common symptom was itchiness (70.28%), most patient sought treatment after the complaint have been persisted for more than 30 days (51.7%), and 66.4% patients have family members with similar complaint. Most of the lesions were found on the hands (60.37%), mostly as papules (73.2%). Almost all of them did not undergo a skin scraping examination (99.1%). The most common therapy combination was permethrin 5% and oral antihistamine (49.7%). Conclusions: This profile on scabies patients was expected to aid in improving scabies treatment in the future.